Evaluation of 137Cs, 133Xe and 3H activity concentrations monitored in the Arctic atmosphere - Zhang, Weihua; Paatero, Jussi; Leppänen, Ari-Pekka; Møller, Bredo; Jensen, Louise Kiel; Gudnason, Kjartan; Sofiev, Mikhail; Anderson, Pål; Sickel, Morten; Burakowska, Agnieszka; Kubicki, Marek; Anderson, Amanda (Elsevier, 2022)
This paper provides a brief introduction to the Arctic atmospheric radioactivity monitoring network. A decade of monitoring results have shown the 137Cs background levels in Arctic air range from 0.05 to 1.50 μBq/m3. The monitoring stations have sufficient sensitivity to detect 137Cs brought to the atmosphere due to resuspension in local soil and reemissions from biomass burning in a daily temporal resolution. These observations can be used as tracers for atmospheric processes. The 133Xe measurements obtained at Yellowknife, Resolute and Spitsbergen could support other research into how air pollution problems arise across intercontinental distances. It will help develop and improve models capable of predicting the long-distance transport and deposition of trace gases in the Arctic. Rainwater monitoring data collected in Finnish Lapland since the 1960’s indicate that 3H radioactivity concentrations reached natural background levels in early 2000s, typically around 1–2 Bq/L monthly, with an annual seasonal variation cycle consistent with the observed of other cosmogenic radionuclides.